Coconut shell as partial replacement of fine and coarse aggregate in concrete - Sazliana Sahima, Sidek (2017)
In the construction industry, the increase in construction material cost is one of the greatest impact to the society. Therefore, there is a need to study on sustainable material in concrete to produce more environmental friendly and sustainable product using waste material. The potential use of agricultural waste in civil engineering and building construction works have been investigated by various researchers. Coconut waste is one of the waste generated by the agricultural process which led to the disposal and management problem that pose a serious challenge towards environmental issues. Malaysia has produced around 555,120 tons, metric by coconut waste. Thus, the highest number of waste will be generated and it is quite worrying to manage huge numbers of coconut waste. The use of coconut shell can help to prevent illegal dumping that cause environmental problems. Aggregate is the main constituent of concrete mix, hence in this study, coconut shell as partial replacement of fine and coarse aggregates were presented and discussed. In this study, the coarse and fine aggregates were partially replaced by coconut shell with percentages replacement of (0%, 2.5%, 5.0%, 7.5% and 10%). The mechanical properties tests considered in this study, including compressive, splitting tensile and flexural strength. Results show that, the compressive strength of 0%, 2.5%, 5.0%, 7.5% and 10% coconut shell replacement achieved the compressive strength of 36.66, 30.93, 29.20, 28.33, 27.34 N/mm2, respectively. Findings showed that the optimum percentage of aggregate replacement was 2.5%. Hence, splitting tensile and flexural strength are casted using 2.5% replacement of aggregates. Result of splitting tensile strength test attained a maximum strength of 2.68 N/mm2, 6.8% lower than control cylinders sample. Meanwhile, flexural strength achieved 6.13 N/mm2,14.6% higher than the control beams. These results show that coconut shell concrete can be used as fine and coarse aggregates replacement in which reduced cost and eco-friendly.